FORMATION OF ATOLL GARNET IN THE ARDARA AUREOLE, NW IRELAND (Journal of Sciences, Islamic Republic of Iran)
The formation of atoll garnet in the Ardara aureole, NW Ireland, is discussed using the textural, chemical and Electron Backscatter Diffraction (EBSD) data. Textural evidence suggests the possibility of incipient of garnet replacement from the core. In addition, the presence of staurolite and andalusite in the core of small atoll garnets as well as the occurrence of sillimanite in the core of large atoll garnet reveal the prograde nature of atoll formation. The microprobe analyses and EBSD data also indicate that atoll garnets in the Ardara aureole developed by pre-existing idioblastic garnets being replaced by mainly biotite to produce atoll forms.